2012
DOI: 10.1016/j.joi.2012.04.003
|View full text |Cite
|
Sign up to set email alerts
|

An international comparison of journal publishing and citing behaviours

Abstract: The relationship between researchers" publishing and citing behaviours has received little examination despite its potential importance in scholarly communication, particularly at an international level. To remedy this we studied documents and their references indexed in Thomson Reuters"s Web of Science (WoS) in the period 2000-2009 to compare journal publishing behaviours against journal citing behaviours across the world. The results reveal that most publications in, and citations to, all five quality based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…By the same token, national-culture driven attitudes, social perceptions, preferences and behavioral responses have been shown to bring about diversity in the scholarly communication practices of scholars from different countries, most notably between developed countries at the centre of world science and developing countries, on the periphery of the global scientific enterprise Xu;Nicholas, 2017;Didegah;Thelwall;Gazni, 2012;Haddow;Hammarfelt, 2019;Jamali et al, 2014;Jamali et al, 2020b;Xu et al, 2015). In the specific case of open access publishing, as Guédon (1975) predicted nearly half a century ago, the opportunities afforded by OA for scientists-as-authors often deepen the schism between rich and poor countries.…”
Section: The Factors Shaping Researchers' Uptake Of Open Access Publishingmentioning
confidence: 99%
“…By the same token, national-culture driven attitudes, social perceptions, preferences and behavioral responses have been shown to bring about diversity in the scholarly communication practices of scholars from different countries, most notably between developed countries at the centre of world science and developing countries, on the periphery of the global scientific enterprise Xu;Nicholas, 2017;Didegah;Thelwall;Gazni, 2012;Haddow;Hammarfelt, 2019;Jamali et al, 2014;Jamali et al, 2020b;Xu et al, 2015). In the specific case of open access publishing, as Guédon (1975) predicted nearly half a century ago, the opportunities afforded by OA for scientists-as-authors often deepen the schism between rich and poor countries.…”
Section: The Factors Shaping Researchers' Uptake Of Open Access Publishingmentioning
confidence: 99%
“…Similar trends in the low representation of LAMIC research have been reported in many other health and bio-medical subject areas. 1318 While the general trend has been a parallel and corresponding increase in both the amount of LAMIC research and their representation in international academic publication outlets, the rate of increase, ease of publication, acceptance rates of manuscripts, and especially those solely authored by LAMIC researchers remain significantly low. In addition, a “transatlantic divide” in LAMIC research publishing has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Didegah et al undertook an international comparison of journal publishing and citing behaviors. They studied documents and their references indexed in Web of Science (WoS) in the period 2000-2009, and compared journal publishing behaviors against journal citing behaviors by scientists from different countries [Didegah, Thelwall, & Gazni, 2012]. In a sample of economics journals, Frandsen presented a method of citation analysis based on multiple linear regression for both cited and citing journals.…”
Section: Introductionmentioning
confidence: 99%